Analysis of Berthing Safety using Maneuvering Simulation and Berthing Aid System - I Putu Sindhu Asmara; Muh. Anis Mustaghfirin; Kharis Abdullah; Cahya Ardie Firmansyah (International Journal of Marine Engineering Innovation and Research, 2025)
Collisions of ships to cranes in container terminals are attracting attention from the maritime safety community. This paper provides a berthing safety analysis using the berthing aid and automatic identification systems. First, a berthing aid system is developed to measure berthing safety, as speed and angle indicate. The berthing aid system installed in a berth consists of two laser sensors to measure ships' distances, speed, and heading during the berthing maneuver. Second, a berthing maneuver simulation is conducted to determine tugboat elements, consisting of the number and capacity of tugboats, using a time series of thrust power and direction. The elements are simulated to achieve the berthing safety indicated by the time series of speed over the ground, course over the ground, and the ship's heading angle relative to the berth. The monitoring of ship trajectory using an automatic identification system in the port area and berthing safety parameters along the end stage of the berthing maneuver using the berthing aid system has been implemented in this research. The measurement proved that the berthing maneuvers comply with the requirements.